2018
DOI: 10.1039/c7cp08636a
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electronic and adhesion characteristics of zinc/silica interfaces: ab initio study on zinc/β-cristobalite

Abstract: The weak interaction between zinc and silica is responsible for a poor performance of anti-corrosive galvanic zinc coatings on modern advanced high strength steels. With the goal of identifying its microscopic origin, we report an extensive ab initio study on the structural, electronic, and adhesion characteristics of a variety of model zinc/β-cristobalite interfaces, representative for different oxidation conditions. We show that the weakness of the zinc-silica interaction at non polar interfaces is driven by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…Beyond the existing studies treating interfaces of different silica polymorphs with Cu, Ni, Al, Ag, and Pt, [25][26][27][28][29][30][31][32][33] we have recently analyzed zinc/β -cristobalite interfaces. 34 We have shown that the characteristics of the interface are very sensitive to the silica surface composition and structure. The stoichiometric terminations show a reconstruction which saturates all dangling bonds by forming two-membered siloxane rings, which have also been identified on dehydroxylated amorphous silica surfaces.…”
Section: Introductionmentioning
confidence: 94%
“…Beyond the existing studies treating interfaces of different silica polymorphs with Cu, Ni, Al, Ag, and Pt, [25][26][27][28][29][30][31][32][33] we have recently analyzed zinc/β -cristobalite interfaces. 34 We have shown that the characteristics of the interface are very sensitive to the silica surface composition and structure. The stoichiometric terminations show a reconstruction which saturates all dangling bonds by forming two-membered siloxane rings, which have also been identified on dehydroxylated amorphous silica surfaces.…”
Section: Introductionmentioning
confidence: 94%
“…We recall that the zinc/silica interface is very weak, with a separation energy of 0.5 J m −2 or lower, due to the reconstruction of the silicate surface and the formation of weakly interacting siloxane rings. 10 If compared to the calculated separation energy in bulk zinc (1.05 J m −2 ), this clearly shows that the poor performance of zinc coatings to the silica-covered steels is due to the interfacial cleavage at the weaklyinteracting metal/oxide interface. Our present computational results show that zinc/silicate interfaces systematically show much better adhesion characteristics, with E sep twice or more larger compared to the zinc/silica one (see Tab. 3).…”
Section: Discussionmentioning
confidence: 81%
“…10 ), and thus somewhat smaller than the breaking energy within bulk zinc. However, we remind that the SiO 2rich silicate surfaces and the associated interfaces with zinc are thermodynamically less sta- It is also worthwhile to compare zinc adhesion at silicate surfaces with that at oxygen-rich silica surfaces which can be obtained by silica pre-hydroxylation followed by interface dehydrogenation 10,11 . In this latter case, a larger density of Zn-O bonds is formed than at the silicate/zinc interfaces (24.8 bonds/nm 2 , to be compared with 6.2 at the Zn 2 O 2 silicate/zinc interface), which translates in a very strong interfacial adhesion.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations